A new species of Rhynchosia (Leguminosae, Papilionoideae) from Bahia State, Brazil - Bezerra, Luísa Maria De Paula Alves; Oliveira, Ana Carla Da Silva; Santos Silva, Juliana; Vargas, Wanderleia De; Cândido, Elisa Silva; Monteiro, Thiago Cobra E; Vatanparast, Mohammad; Fortuna Perez, Ana Paula (Phytotaxa, 2019)
During a taxonomic study of Rhynchosia in Brazil and intensive field work, a new species from Bahia, R. lewisii, was discovered. The new species is herein described, illustrated and its morphological affinities with related species are presented. Additionally, the conservation status of the new species is discussed, and a key to the taxa of Rhynchosia that occur in the Bahia is provided.